The process design of water quenching based on finite element simulation and its applications. Issue 1 (2nd January 2020) - Zuo, Xunwei; Liu, Yu; Chen, Nailu; Rong, Yonghua
ABSTRACT: Quenching is a widely used process in heat treatment enterprises. Clean and cheap water quenching instead of high pollution and high cost of oil quenching or polymer aqueous solution quenching will become a trend in these enterprises. However, since the cracking problem of alloy steel parts induced by water quenching with high cooling rate has not been solved, the oil and polymer aqueous solution with low cooling rate are still widely used in various countries in the world. Water–air alternative timed quenching' process and differential time grading quenching process proposed by us have been successfully applied to treat various large-size alloy steel parts in China. In this review paper, we will introduce the face issues in the design of these two kinds of processes based on finite element simulation (FES): (1) Main factor affecting accurate prediction of quenching stress; (2) The method to determine the optimizing process. Two engineering examples are selected to clarify how to solve the cracking issues of alloy steel part by FES.